1993
DOI: 10.1093/jn/123.9.1504
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Chromium Supplementation with or without Somatotropin Treatment Alters Serum Hormones and Metabolites in Growing Pigs without Affecting Growth Performance

Abstract: Twenty-four castrated male pigs were used in a 2 x 2 treatment array to determine the main effects of and interactions between dietary chromium supplementation and pituitary porcine somatotropin (ppST) administration on growth performance and serum hormone and metabolite concentrations. The treatments were 1) control (basal diet); 2) chromium (basal diet+300 micrograms/kg diet added trivalent chromium as chromium picolinate); 3) ppST (100 micrograms/(kg body wt.d); and 4) chromium+ppST. Treatments were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
4
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 16 publications
5
34
4
5
Order By: Relevance
“…The increased serum cortisol by addition of 1 200 ppb Cr from CrNano in the present study suggests that high level of Cr may be a stressor to rat. There is no change in serum GH levels due to supplemental Cr as CrNano, which was inconsistent with Evock-Clover et al(1993) who reported an increase of plasma GH in pigs by dietary addition of CrPic.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The increased serum cortisol by addition of 1 200 ppb Cr from CrNano in the present study suggests that high level of Cr may be a stressor to rat. There is no change in serum GH levels due to supplemental Cr as CrNano, which was inconsistent with Evock-Clover et al(1993) who reported an increase of plasma GH in pigs by dietary addition of CrPic.…”
Section: Discussioncontrasting
confidence: 71%
“…Page et al(1993) reported that longissimus muscle area and percentage of muscling were increased and 10th rib fat was decreased by chromium picolinate (CrPic) added to the diets of growing-finishing pigs. However, inconsistent or no effect on carcass traits with supplementation of CrPic and chromium chloride (CrCl 3 ) was also reported (Evock-Clover et al, 1993;Mooney and Cromwell, 1997). In human, there were also reports of increased muscle mass and decreased body fatness due to Cr supplementation (Evans, 1989;Bulbulian et al, 1996;Kaats et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Mooney and Cromwell (1995) observed that Cr-PIC supplementation throughout the entire growing-finishing phase tended to improve growth rate and significantly increased the protein:fat ratio of the carcass. On the other hand Cr supplementation at 300 µg kg -1 of diet as Cr-PIC did not show any improvement in growth rate and feed efficiency (Evock-Clover et al 1993).…”
Section: Growth Performancementioning
confidence: 74%
“…Researchers (Evock-Clover et al 1993;White et al 1993) have indicated that feeder pigs fed CrPic had decreased serum insulin and glucose concentrations because it was believed that chromium may work as a cofactor with insulin. The increased insulin receptor sensitivity and increased protein synthesis in muscle may to some extent explain the mechanism of the observed increased muscling and reduced lipogenesis in swine supplemented with chromium.…”
mentioning
confidence: 99%